Studi Komparasi Sistem Pendidikan di Norwegia dan Amerika Serikat - Anshori; Sassi, Komaruddin (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2023)
This article was written with the aim of conducting a comparative study of the education systems in Norway and the United States, by conducting an in-depth study of the education systems in each country, then analyzing the similarities and differences in the education systems of the two countries. To carry out data and information mining in this research, the author uses a literature study in which the literature is taken in accordance with the subject matter and analyzed in depth so that conclusions and findings can be drawn in the research. From the results of this research, the author concludes that: (1) The similarities between the education system in Norway and the education system in the United States, both countries have a diverse and inclusive approach and emphasize the development of social and critical skills;(2) The difference between the education system in Norway and the education system in the United States, in Norway it emphasizes more flexibility and holisticness, while the United States is more structured and follows standards. As for the aspect of the teaching approach, Norway focuses more on active learning, while the United States has a combination of traditional and innovative approaches.